Discovery of Novel Potent Small Natural Molecules Able to Enhance Attenuation of the Pathobiology of Gastric Cancer-Associated Helicobacter pylori by Molecular Modeling - Satapat Racha (2018)
© 2018 Springer Nature B.V. CagA is an oncoprotein that plays a significant role in the advancement of gastric cancer by interacting with phosphatidylserine of host cell plasma membrane. This protein is a potential target for the cancer therapy. In the present study, the initial and dynamic binding interaction mechanisms between CagA and herbal compounds were investigated by molecular docking of the 38 compounds followed by an analysis combining molecular dynamics simulations and molecular mechanics–Poisson Boltzmann surface area binding free energy calculations of the top four hit compounds; spinasterol, luteoxanthin, 3′-prenylrubranine and neoxanthin. Energetic analyses disclosed binding free energies pointing out that neoxanthin and luteoxanthin were potential candidates as lead compounds in drug development towards the CagA–phosphatidylserine inhibitors. Ultimately, binding free energy decomposition gave detailed information regarding the essential amino acid residues stabilizing the complexes.